175th anniversary of Bochdalek's inaugural dissertation - Cech, Pavel; Kachlik, David (Biomedical papers, 2009)
BACKGROUND: In 2008, it has been 175 years since the publication of Vincenc Alexandr Bochdalek's thesis.RESULTS: On October 22, 1833 he defended his inaugural dissertation in the Greater Hall of Carolinum in Prague and six days later he got his degree in the Lesser Hall of Carolinum. The dissertation was called Anleitung zur praktischen Zergliederung des menschlichen Gehirnes (A guide of the practical dissection of the human brain). It consisted of an introduction (11 pages), main section (208 pages) and an appendix with 19 defended theses. They was aimed not only at anatomy, but also at various fields of medicine, e.g. atmosphere study, treatment of tetanus by usage of antiphlogistics, comparison of the effects of venesection and drainage of the ascites, blockage of the lacrimal duct etc. Bochdalek pointed out that resorption did not occur via blood veins but via lymph vessels; presented his own views of the nerve function, denied the statement that both eye chambers were lined with the Demours' membrane; warned of overestimating the results of experiments upon animals; contemplated over the indication of the Cesarean section of the dead pregnant women; appealed not to separate the lunatic asylums from hospitals and recommended to dissect brains of the dead lunatics.CONCLUSIONS: Although some of Bochdalek's opinions mentioned in the defended theses have been unconfirmed by modern science, this only Bochdalek's monography remains to serve as a proof of one of his findings (flower basket) which later acquired an eponym.
Keywords: Bochdalek/Biography/History of medicine